Brand Awareness, Brand Image, Perceived Value, and Perceived Quality Towards Brand Loyalty - Steven Steven; Tommy Setiawan Ruslim (Graduate Program of Universitas Tarumanagara, 2023)
Fast fashion is one of a lot of interesting topics to talk about and an industry that never dies. So, the purpose of this research was to examine the effect of BA, BI, PV, and PQ towards BL on H&M consumers in Jakarta. The population is H&M consumers with a total of 309 respondents. The method used in distributing the questionnaires is a purposive sampling method. The questionnaires are distributed online in google form and then the data were analyzed using Smart]PLS software version 3.3.3. The results of the data show that BI, PV, PQ has a positive effect on BL on H&M consumers in Jakarta. Meanwhile, BA not has a significant effect on BL on H&M consumers in Jakarta.